Dark fermentative biohydrogen production by Clostridium butyricum using cashew apple bagasse hydrolysate: Effect of glucose and glycerol modulation - Estefânia de Sousa Moreira; Carlos Alberto Chaves Girão Neto; Carla Luzia Borges Reis; Gabriel Facundo Simão; Luca Micoli; Maria Valderez Ponte Rocha (Biomass and Bioenergy, 2026)

Tectono-stratigraphic evolution of a subducted Tonian continental margin in the western São Francisco paleocontinent (Passos Nappe, SE Brazil): Insights from lithogeochemistry, Sr-Nd isotopes, and detrital zircon U-Pb ages - Gabriel Paravidini; Claudio de Morisson Valeriano; Luiz Sérgio Amarante Simões; Catherine Mottram; Rob Strachan; Glenn Chapman; Henrique Bruno; Monica Heilbron; Paulo Henrique Amorim Dias; Sandro Mauri; Carla Neto; Craig Storey (Journal of South American Earth Sciences, 2026)

Use of honey-derived silver nanoparticles associated with low-level laser therapy for bone defect repair in rats - Armélio Vasconcelos de Siqueira Neto; Ana Claudia Souza Abreu; Carla Beatriz dos Santos Torres; Mônica Patrícia de Sousa Rêgo; Hugo de Campos Braga; Alan Kelbis Oliveira Lima; Emerson Cristi de Barros; Kashif Gul; José Arnaldo Santana Costa; Arthur Abinader Vasconcelos; Donald Fernandes; Paulo Sérgio Taube (Journal of Photochemistry and Photobiology B: Biology, 2026)

The role of post-flood climate disaster in southern Brazil and its impact on the atmospheric remobilization of trace elements and particulate matter - Kassiano S. Sousa; Antonio Azeredo; Gilberto Fillmann; Adan S. Lino; Rodrigo O. Meire; Daniela C. Oliveira; Janeide Padilha; Enrico M. Saggioro; Carla Sirtori; Suélem Soares; Cláudia Teixeira; José Araújo Souto-Neto; et al. (Atmospheric Pollution Research, 2026)

A new Plasmodium Marchiafava & Celli, 1885 (Apicomplexa: Haemosporida) species in Cory’s Shearwater (Calonectris borealis) [Cory]) (Aves: Procellariiformes) stranded in a coastal area in Brazil - Carolina Clares dos Anjos; Bruna Antonetti Damato; Raquel Beneton Ferioli; Angélica M. Sánchez-Sarmiento; Amanda R. da Mata; Carla B. Barbosa; Hugo Gallo Neto; Carolina Romeiro Fernandes Chagas; Gediminas Valkiūnas; Karin Kirchgatter (Systematic Parasitology, 2026)
Cory’s Shearwater ( Calonectris borealis ), a migratory seabird from the Procellariidae family, is widely distributed across the Atlantic Ocean. It breeds on islands of Azores, Madeira, Canary, and Berlengas, and winters in coastal areas of South America and Africa. This species’ wide habitat range contributes to pathogen exchange across global regions. Plasmodium , a genus of apicomplexan parasites causing avian malaria, affects many wild bird species worldwide. Although rare in seabirds, Plasmodium infections can significantly impact these hosts. We identified and characterized a new Plasmodium species in an adult male C. borealis found live-stranded on the northern coast of São Paulo, Brazil, during the daily activities of the Santos Basin Beach Monitoring Project (PMP-BS). The bird was rescued and kept in rehabilitation for 61 days but was euthanized due to poor prognosis. Blood smears revealed parasitemia varying from 0.04% until 2.09%. Blood and tissue samples were tested using PCR targeting a cytochrome b ( cytb ) gene fragment. The obtained sequence was 100% similar to Plasmodium lineage pLK06. Phylogenetic analysis placed the parasite within the Novyella clade, with morphological features closely related to P. vaughani . Necropsy showed hepato- and splenomegaly, while histopathology confirmed hepatitis and pulmonary hemorrhage. These findings, combined with clinical relapse despite anti-malaria treatment, indicate the parasite’s pathogenicity in C. borealis . This represents the first haemosporidian infection in this seabird and the first identification of the pLK06 lineage in Procellariiformes, resulting in the description of Plasmodium borealis sp . nov . These findings expand knowledge of parasite diversity in seabirds and highlight the need for continued surveillance in understudied avian groups.

In vitro biological and functional properties of fermented roasted coffee extracts in the context of Parkinson's disease - Dionisio Pedro Amorim-Neto; Joao Victor Virgilio-da-Silva; Jaqueline Sousa Correia; Matheus Péricles Silva Láscaris; Jhonathan Vinícius Menezes Silva; Carla Alves Barbosa; Beatriz Dal Pian Machado; Mauricio Luis Sforça; Gustavo Henrique Rodrigues da Silva; Lilian Regina Barros Mariutti; Pedro Manoel Mendes Moraes-Vieira; Cesar Renato Sartori; et al. (Food Bioscience, 2026)

Chemical analysis and biological activity of crude extracts obtained from leaves of Passiflora foetida (Subg. Passiflora ) and Passiflora morifolia (Subg. Decaloba) - Ohana Luiza Santos de Oliveira; Oscar Caetano da Silva Neto; Gabriele Rodrigues Conceição; Fábio Alexandre Chinalia; Daniel Pereira Bezerra; Milena Botelho Pereira Soares; Valdenizia Rodrigues Silva; Luciano de Souza Santos; Carla Junqueira Moragas Tellís; João Victor da Silva e Silva; Caroline Conceição da Guarda; Jorge Mauricio David; et al. (Natural Product Research, 2026)

Bacterial diversity in ferruginous duricrust (canga) and the physicochemical variables affecting their prevalence, distribution and predicted metabolic pathways - Viviane Faria Morais Jotta; Carla Alessandra Silva; Glen Jasper Yupanqui García; Andrea Rodrigues Marques; Andria dos Santos Freitas; Aristóteles Góes-Neto; Fernanda Badotti (Antonie van Leeuwenhoek, 2026)
The ferruginous duricrust ( canga ) in the Iron Quadrangle (IQ), Minas Gerais, Brazil, occurs within the Campo Rupestre and presents remarkable levels of endemism and species richness. Despite the recognized importance of microorganisms for the maintenance of this ecosystem, current molecular-based studies reveal that both the taxonomic composition and the ecological functions of the canga microbiome are undiscovered. In this study, eighteen samples of canga were collected from the Serra da Piedade State Natural Monument, and their taxonomic diversity was investigated using 16S rRNA metabarcoding. Additionally, the influence of physicochemical variables on microbial diversity and community structure was estimated using statistical tools. Most of the 856,667 reads clustered into ASVs corresponded to Bacteria (99.7%), and the most abundant of the 184 identified genera were Conexibacter , Acidothermus and Bryobacter . Microbial diversity was explained by a combination of physicochemical variables, such as organic matter (OM), iron (Fe), aluminum (Al) and pH, whereas microbial community structure was influenced by the concentrations of Fe, Al and the cation exchange capacity (CEC). Functional prediction analysis based on the main genera identified in the samples indicated that the denitrification pathway may play an important role in the ecosystem. The investigation of the genera and their metabolic pathways based on the literature revealed that they are unexplored and emphasized the biodiversity hotspot yet to be explored in ferruginous duricrust. Therefore, our results reinforce the importance of further studies in this environment, both for future biotechnological applications and for appropriate management and preservation actions.

A synthesis on the spread of the tailing plumes resulting from the Fundão dam collapse along the Brazilian coast: Integrating evidence from multiple sources - Rafael Barros Pereira Pinheiro; Aliny P.F. Pires; Carla Grigoletto Duarte; Raphael M. Macieira; Danielle Gama-Maia; Mário Almeida-Neto; Lucia Fernandes Sanches; Rafael Loyola; Stella Manes; Adriano Sanches Melo (Marine Pollution Bulletin, 2026)

In vitro and in silico evaluation of nematicidal lectin compounds from Artocarpus heterophyllus seeds targeting gastrointestinal helminths - Renata Cristina Borges da Silva Macedo; Mirna Samara Dié Alves; Francisco Chagas Barbalho Neto; Pablo Leandro Filgueira Feitosa; Mário Luan Silva de Medeiros; Edgley Alves de Oliveira Paula; Michele Dalvina Correia da Silva; Ana Carla Diógenes Suassuna Bezerra (Veterinary Parasitology, 2026)

Effects of soil nutrient enrichment on biomass, herbivores, and their predators differ between tree species in the Brazilian Cerrado - Carla Faleiro Tinoco; Sílvia Castro; Rodrigo Damasco Daud; Vanessa Leonel Falchi; Júlia Almeida Reis; Stefany Ribeiro Constantino; Carlos de Melo e Silva-Neto; Luísa Gigante Carvalheiro (Oecologia, 2026)
Human-induced changes in nitrogen (N) and phosphorus (P) global cycles and availability significantly impact plant growth and nutritional composition, thereby affecting ecosystem dynamics. However, research on the effects of increased nutrient availability often focuses on plant community-level effects, overlooking interspecific variability and neglecting impacts on higher trophic levels. Using a controlled fertilization experiment with six tree species that naturally occur in the Cerrado biome (Brazilian savannas), we showed that there is substantial interspecific variation in how plants respond to nutrient changes. This reflects the existence of competitive advantage for certain native species under a scenario of increased soil nutrient availability. Such effects propagated to higher trophic levels (herbivores and their predators), also varying between plant host species. The strength and direction of N input effect depended on P levels and the type of herbivores. Large invertebrate leaf herbivores were less affected than phytophagous mites. Impacts on higher trophic levels (predatory mites) were less pronounced than on phytophagous mites. Overall, we show that ongoing soil nutrient enrichment has the potential to alter interspecific competition dynamics in plant communities with consequences for ecological interaction partners. These findings have important implications for conservation and ecosystem management, especially in areas highly exposed to soil nutrient enrichment due to farming and industrial activities.

Heatwaves in the Northern Brazil Region: Current and Future Perspectives - Felipe Jeferson de Medeiros; Samyr Barata Chebly; Glícia Ruth Garcia de Araújo; Francisco Agustinho de Brito Neto; Kellen Carla Lima (International Journal of Climatology, 2025)
Heatwaves (HWs) characteristics (number, frequency and duration) in state capitals of the Northern Brazil Region (NBR) and their climate projections throughout the century were analysed using observed data from meteorological stations and Regional Climate Models (RCMs). HWs were identified considering a minimum period of three consecutive days during which the daily maximum temperature exceeds the 90th percentile. Results showed that more than 125 HWs were recorded in each NBR capital between 1980 and 2019. On average, these HWs were observed over a span of 17–21 days per year, with individual events typically lasting between 3 and 5 days. In the last four decades (1980–2019), the number of HWs as well as their frequency and duration have increased over the NBR. Regarding the model's performance, the HWs characteristics could be reasonably reproduced by the ensemble generated by the RCM from the CORDEX‐CORE. However, the errors found led us to apply a bias‐correction method to produce a fair indication of the future changes. In a future perspective considering the most pessimistic scenario (RCP8.5), HWs are projected to increase in number, frequency, and duration in almost all capitals, with these conditions expected to worsen by the end of the century. The projected intensification suggests that the number of HWs could more than double in most NBR capitals, while the increase in frequency and duration can exceed 600% and 300%, respectively. These regional projected changes reinforce the need for deep, rapid and sustained mitigation and accelerated implementation of adaptation actions to contain and reduce global warming and its related impacts and risks for humans and ecosystems.

Chemical and toxicological evaluation of micropollutants degradation in tertiary municipal wastewater by H2O2/UVC - Gabrielly M. Santos; Lucas G. Costa; Eduardo O. Marson; Meliza A.S. Bessa; Raquel W. Becker; Carla F.G. Frois; Carla Sirtori; Adão S. Ferreira; Raquel M.F. Sousa; Waldomiro Borges Neto; Marcelo B. Santos; Solidônio R. Carvalho; et al. (Journal of Environmental Chemical Engineering, 2025)

Modification of cornstarch: Influence of the addition of sodium chloride, carbonate and phosphate combined with a pulsed electric field - Raphael Lucas Jacinto Almeida; Newton Carlos Santos; Jessica Renaly Fernandes Morais; Cecilia Elisa Sousa Muniz; Lucas Wallyson Pereira de Queiroz; Maely Jezzer Cândido Venâncio; Osmar Batista de Souza Neto; Ynis Thaciane Felix da Silva; Martha Maria Gomes Nóbrega; Bárbara Freire de Oliveira; Juliana Cruz Albuquerque; Ana Carolina Nóbrega Leite; et al. (Food Chemistry, 2025)

Beyond the scrotal circumference: Exploring phenotypic, nutritional and metabolic traits associated with early sexual development in young Nelore (Bos indicus) bulls - Bruna Lima Chechin Catussi; Romulo Germano de Rezende; Pedro Nacib Jorge-Neto; Laura Nataly Garcia-Oliveros; Emanuele Almeida Gricio; Lucas Oliveira e Silva; Eneiva Carla Carvalho Celeghini; Pietro Sampaio Baruselli (Theriogenology, 2025)

The silent adjuvant interaction on the predatory behavior and video tracking with computerized analysis on Marava arachidis (Yersin) (Dermaptera: Labiidae) - Taiane G.F. da Silva; Angélica da Silva Salustino; Jaime G. da Silva Neto; Jacinto de L. Batista; Érica K. de Araújo; Iago V.I. da Silva; Carla R.S.M. Viagem; Luciana B. Silva; Carlos H. de Brito; Khyson G. Abreu; Robério de Oliveira; José B. Malaquias (Environmental Pollution, 2025)

Chronic Exercise Protects Against Cognitive Deficits in an Alzheimer’s Disease Model by Enhancing Autophagy and Reducing Mitochondrial Abnormalities - Gustavo Paroschi Morais; Ivo Vieira de Sousa Neto; Allice Santos Cruz Veras; Giovana Rampazzo Teixeira; Luciana Oliveira Paroschi; Ana Paula Pinto; Jonathas Rodrigo dos Santos; Luciane Carla Alberici; Dennys Esper Corrêa Cintra; José Rodrigo Pauli; Ana Paula Morelli; Eduardo Rochete Ropelle; et al. (Molecular Neurobiology, 2025)

Moderate pasture intensification enhances soil organic carbon stocks in a degraded Brazilian Ferralsol - Lucas Raimundo Bento; João Vitor dos Santos; Steffen A. Schweizer; Carla Pereira de Morais; Milene Corso Mitsuyuki; Patrícia Perondi Anchão Oliveira; José Ricardo Macedo Pezzopane; Alberto Carlos de Campos Bernardi; Ladislau Martin-Neto (Soil and Tillage Research, 2025)

Contamination by Potentially Toxic Elements (PTEs) in Agricultural Products Grown Around Sepetiba Bay, Rio de Janeiro State (SE Brazil) - Graziele Arantes Reis; Maria Virginia Alves Martins; Lisia Maria Gobbo Santos; Santos Alves Vicentine Neto; Fernando Barbosa Junior; Mauro Cesar Geraldes; Sérgio Bergamaschi; Rubens Cesar Lopes Figueira; Carla Patinha; Eduardo Ferreira da Silva; Fernando Rocha (Archives of Environmental Contamination and Toxicology, 2025)
The contamination of soil, water, and air by potentially toxic elements (PTEs) allows the transfer of metals to food. When introduced into food through soil, PTEs are absorbed by plant roots and transported to the bloodstream. The region surrounding Sepetiba Bay (SB), a densely populated area intensively exploited for tourist purposes, is one of the most contaminated by PTEs in the southeastern region of Brazil. Therefore, this study aims to evaluate (by ICP-MS) the concentrations of PTEs in agricultural products (roots, fruits, leaves, seeds, cheese, and eggs) cultivated and sold by rural producers in the region surrounding SB. The 26 food types selected for this study were produced in this region and purchased at local markets. The results for the analyzed foods revealed relatively high concentrations of Zn > Cu > Ni > Cr > As > Pb > Co > Hg > Cd, exceeding the limits established by ANVISA and international laws. Cluster analysis (CA) and principal component analysis (PCA) grouped the PTEs according to their possible sources: ore transport (Zn, Cu, Pb, and Cd), natural (Hg, Cr, and Ni), and fertilizers (Co and As). The CA allowed us to distinguish two main food groups in terms of the enrichment of PTEs. Group 1 contains leaves, animal products, and seeds with higher levels of Hg, Cr, Ni, Co, and As. Group 2 includes roots and fruits, which have higher concentrations of Zn, Cu, Pb, and Cd than Group 1. The Hazard Quotient (HQ) suggests that As and Cr pose a higher risk in foods of CA-Group 1 (leaves, animal products, and seeds). Hazard Index (HI) values > 1 indicate a risk of probable long-term carcinogenesis in adults. Thus, this study reveals that the continued consumption of food produced in the region surrounding SB could cause health problems for the local population.

Action of Biotic Elicitors on Cherry Tomato Under Saline Stress: Physiological and Biochemical Variables - Marlenildo Ferreira Melo; Patrícia Lígia Dantas de Morais; Hozano de Souza Lemos Neto; Carla Sonale Azevedo Soares Silva; Nildo da Silva Dias; Marciana Bizerra de Morais; Eveline Nogueira Lima (Journal of Plant Growth Regulation, 2025)

Cinnamon powder intake enhances the effect of caloric restriction on white adipose tissue in male rats - Lia Rafaella Ballard Kuhnert; Roberta da Fonseca Coutinho Pontes; Jessika Geisebel Oliveira Neto; Juliana Santos Romão; Carla Eponina de Carvalho Pinto; Karen Jesus Oliveira (Journal of Molecular Histology, 2025)

Unveiling early-stage responses of sensitive traits to water stress in tropical maize: a characterization study of a public panel - Ingrid Pinheiro Machado; Fernanda Carla Ferreira de Pontes; Maria Valnice de Souza Silveira; Antônio Lucas Aguiar Lobo; Michele Jorge Silva Siqueira; Roberto Fritsche-Neto; Júlio César DoVale (Euphytica, 2025)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Magnesium, selenium and zinc deficiency compromises antioxidant defense in women with obesity - Ana Raquel Soares de Oliveira; Kyria Jayanne Clímaco Cruz; Jennifer Beatriz Silva Morais; Loanne Rocha dos Santos; Stéfany Rodrigues de Sousa Melo; Larissa Cristina Fontenelle; Juliana Soares Severo; Jéssica Batista Beserra; Thayanne Gabryelle Visgueira de Sousa; Suelem Torres de Freitas; Emyle Horrana Serafim de Oliveira; Carla Soraya Costa Maia; et al. (BioMetals, 2024)

Coeval TTG and sanukitoid magmatism during the Rhyacian tectonic evolution of the Juiz de Fora Complex (São Francisco Paleocontinent, SE-Brazil) - Sandro Mauri; Monica Heilbron; Henrique Bruno; Samuel Bersan; Rasec Almeida; Rodson de Abreu Marques; Syro Lacerda; Ariadne Marra de Souza; Gabriel Paravidini; Carla Neto; Cláudio de Morisson Valeriano; Glenn Chapman; et al. (Precambrian Research, 2024)

Revisiting decision-making assumptions to improve deforestation predictions: Evidence from the Amazon - Priscila dos Reis Cunha; Camilo Rodrigues Neto; Carla Morsello (Ecological Economics, 2024)

Relationship Between Zinc, Selenium, and Magnesium Status and Markers of Metabolically Healthy and Unhealthy Obesity Phenotypes - Kyria Jayanne Clímaco Cruz; Ana Raquel Soares de Oliveira; Larissa Cristina Fontenelle; Jennifer Beatriz Silva Morais; Stéfany Rodrigues de Sousa Melo; Loanne Rocha dos Santos; Thayanne Gabryelle Visgueira de Sousa; Suelem Torres de Freitas; Gilberto Simeone Henriques; Silvana Bordin; Carla Soraya Costa Maia; Francisco Erasmo de Oliveira; et al. (Biological Trace Element Research, 2024)

Bacterial consortia among Bradyrhizobium species, Azospirillum baldaniorum and Bacillus pumilus promote plant growth and efficient symbiotic nitrogen fixation in mung bean - Vicente Paulo da Costa Neto; Ana Raquel Pereira de Melo; Carla Elisa Sousa Alencar; Victor Breno Campelo de Lima; Jerri Edson Zilli; Artenisa Cerqueira Rodrigues; Aurenivia Bonifacio (Symbiosis, 2024)

Rhyacian-Orosirian transitional arc-collisional magmatism in the Archean Piedade Microcontinent, southern São Francisco Paleocontinent, Brazil - Mariana Carvalho; Henrique Bruno; Samuel Bersan; Craig Storey; Catherine Mottram; Glenn Chapman; Mike Fowler; Claudio Valeriano; Cristiano Lana; Carla Neto; Monica Heilbron (Precambrian Research, 2024)

Glyphosate and aminomethylphosphonic acid metabolite (AMPA) modulate the phenotype of murine melanoma B16-F1 cells - Yvanna Carla de Souza Salgado Kiefer; Marianna Boia Ferreira; Jessica Zablocki da Luz; Francisco Filipak Neto; Ciro Alberto de Oliveira Ribeiro (Environmental Toxicology and Pharmacology, 2024)

Laser-induced breakdown spectroscopy (LIBS) as an analytical tool in precision agriculture: Evaluation of spatial variability of soil fertility in integrated agricultural production systems - Diego V. Babos; Amanda M. Tadini; Carla P. De Morais; Bianca B. Barreto; Mayara A.R. Carvalho; Alberto C.C. Bernardi; Patricia P.A. Oliveira; José R.M. Pezzopane; Débora M.B.P. Milori; Ladislau Martin-Neto (CATENA, 2024)

Linking above and belowground carbon sequestration, soil organic matter properties, and soil health in Brazilian Atlantic Forest restoration - Wanderlei Bieluczyk; Fernanda Ometto Asselta; Deisi Navroski; Júlia Brandão Gontijo; Andressa Monteiro Venturini; Lucas William Mendes; Carla Penha Simon; Plínio Barbosa de Camargo; Amanda Maria Tadini; Ladislau Martin-Neto; José Albertino Bendassolli; Ricardo Ribeiro Rodrigues; et al. (Journal of Environmental Management, 2023)

Optimisation of LDI(+)-FT-ICR MS analysis of asphaltenes to prevent the formation of fullerenes - Victor R. Fonseca; Gabriely S. Folli; Lindamara M. Souza; Thieres M.C. Pereira; Guilherme S.V. Lima; Carla C.B. Viegas; Luiz S. Chinelatto; Álvaro C. Neto; Paulo R. Filgueiras; Valdemar Lacerda; Wanderson Romão (Fuel, 2023)

Telerehabilitation during social distancing for people with Parkinson’s disease: a retrospective study - Erica Tardelli; Acácio Moreira-Neto; Erika Okamoto; Fernanda Rogatto; Mario Vergari-Filho; Egberto Reis Barbosa; Carla Silva-Batista (Acta Neurologica Belgica, 2023)

Sedimentary provenance in continental rifts: U–Pb detrital zircon, Nd and Sr isotopes and lithogeochemistry of the Eocene alluvial sandstones of the Resende Basin, SE–Brazil - Manuela de Oliveira Carvalho; Catherine M. Mottram; Claudio de Morisson Valeriano; Renato Rodriguez Cabral Ramos; Randall Parrish; Joseph Dunlop; Natália Cota; Gabriel Paravidini; Carla Cristine Aguiar Neto; Monica Heilbron; Craig Storey (Sedimentary Geology, 2023)

Ecosystem services generated by Neotropical freshwater fishes - Fernando M. Pelicice; Angelo Antonio Agostinho; Valter M. Azevedo-Santos; Eduardo Bessa; Lilian Casatti; Domingos Garrone-Neto; Luiz Carlos Gomes; Carla S. Pavanelli; Ana Cristina Petry; Paulo dos Santos Pompeu; Roberto E. Reis; Fabio de Oliveira Roque; et al. (Hydrobiologia, 2023)

Efficient microbial cellulose/Fe3O4 nanocomposite for photocatalytic degradation by advanced oxidation process of textile dyes - Rayany Magali da Rocha Santana; Daniella Carla Napoleão; Joan Manuel Rodriguez-Diaz; Rayssa Kelen de Mendonça Gomes; Marina Gomes Silva; Victor Marcelo Estolano de Lima; Antônio Acacio de Melo Neto; Glória Maria Vinhas; Marta Maria Menezes Bezerra Duarte (Chemosphere, 2023)

Saline extract of Portulaca elatior leaves with photoprotective and antioxidant activities does not show acute oral and dermal toxicity in mice - Suéllen Pedrosa da Silva; Clarice Barbosa Lucena da Costa; Anderson Felipe Soares de Freitas; José Dayvid Ferreira da Silva; Wêndeo Kennedy Costa; Wênio Sandoval Filho Lima da Silva; Janaina Carla Barbosa Machado; Sandra Maria Souza da Silva; Magda Rhayanny Assunção Ferreira; Luiz Alberto Lira Soares; Jacinto da Costa Silva Neto; Márcia Vanusa da Silva; et al. (Toxicological Research, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Inflammatory stimulus worsens the effects of UV-A exposure on J774 cells - Orlando Chiarelli-Neto; Michelle Lima Garcez; Christiane Pavani; Waleska Martins; Fernanda Cristina de Abreu Quintela Castro; Roberta Passamani Ambrosio; Flavia Carla Meotti; Mauricio S. Baptista (Journal of Photochemistry and Photobiology B: Biology, 2023)

Inconsistent response of taxonomic groups to space and environment in mediterranean and tropical pond metacommunities - Ángel Gálvez; Pedro R. Peres‐Neto; Andreu Castillo‐Escrivà; Fabián Bonilla; Antonio Camacho; Eduardo M. García‐Roger; Sanda Iepure; Javier Miralles‐Lorenzo; Juan S. Monrós; Carla Olmo; Antonio Picazo; Carmen Rojo; et al. (Ecology, 2023)
The metacommunity concept provides a theoretical framework that aims at explaining organism distributions by a combination of environmental filtering, dispersal, and drift. However, few works have attempted a multitaxon approach and even fewer have compared two distant biogeographical regions using the same methodology. We tested the expectation that temperate (mediterranean‐climate) pond metacommunities would be more influenced by environmental and spatial processes than tropical ones, because of stronger environmental gradients and a greater isolation of waterbodies. However, the pattern should be different among groups of organisms depending on their dispersal abilities. We surveyed 30 tropical and 32 mediterranean temporary ponds from Costa Rica and Spain, respectively, and obtained data on 49 environmental variables. We characterized the biological communities of bacteria and archaea (from the water column and the sediments), phytoplankton, zooplankton, benthic invertebrates, amphibians and birds, and estimated the relative role of space and environment on metacommunity organization for each group and region, by means of variation partitioning using generalized additive models. Purely environmental effects were important in both tropical and mediterranean ponds, but stronger in the latter, probably due to their larger limnological heterogeneity. Spatially correlated environment and pure spatial effects were greater in the tropics, related to higher climatic heterogeneity and dispersal processes (e.g., restriction, surplus) acting at different scales. The variability between taxonomic groups in the contribution of spatial and environmental factors to metacommunity variation was very wide, but higher in active, compared with passive, dispersers. Higher environmental effects were observed in mediterranean passive dispersers, and higher spatial effects in tropical passive dispersers. The unexplained variation was larger in the tropical setting, suggesting a higher role for stochastic processes, unmeasured environmental factors, or biotic interactions in the tropics, although this difference affected some actively dispersing groups (insects and birds) more than passive dispersers. These results, despite our limitations in comparing only two regions, provide support, for a wide variety of aquatic organisms, for the classic view of stronger abiotic niche constraints in temperate areas compared with the tropics. The heterogeneous response of taxonomic groups between regions also points to a stronger influence of regional context than organism adaptations on metacommunity organization.

Nitrogen balance and microbial protein synthesis in dairy cows fed with peanut meal to replace soybean meal - Flávio Soares dos Santos; Ricardo Dias Signoretti; Juliana Silva de Oliveira; Gabriel Teodoro da Silva; Marcelo de Oliveira Alves Rufino; Carla Giselly de Souza; Jessyca Karen Pinheiro; Severino Gonzaga Neto (Tropical Animal Health and Production, 2022)

Sunlight Irradiated Pyrite-Fenton System for Advanced Oxidative Treatment of Textile Dyes Mixture - Rayany Magali da Rocha Santana; Daniella Carla Napoleão; Sérgio Gonzaga dos Santos Júnior; Rayssa Kelen de Mendonça Gomes; Alex Leandro Andrade de Lucena; Graziele Elisandra do Nascimento; Victor Marcelo Estolano de Lima; Antônio Acacio de Melo Neto; Giovanna Machado; Ana Maria Mendonça de Albuquerque Melo; Marta Maria Menezes Bezerra Duarte (Water, Air, & Soil Pollution, 2022)

Spatial analysis of the wing shape of Aedes aegypti mosquito in an endemic dengue area of São Paulo, Brazil - Isaque Prado; Tamara Nunes Lima-Camara; Francisco Chiaravalloti-Neto; Maisa Carla Pereira Parra; Margareth Regina Dibo; Maurício Lacerda Nogueira; Camila Lorenz (International Journal of Tropical Insect Science, 2022)

Molecular and genetic characterization of a large Brazilian cohort presenting hearing loss - Ana Carla Batissoco; Vinicius Pedroso-Campos; Eliete Pardono; Juliana Sampaio-Silva; Cindy Yukimi Sonoda; Gleiciele Alice Vieira-Silva; Estefany Uchoa da Silva de Oliveira Longati; Diego Mariano; Ana Cristina Hiromi Hoshino; Robinson Koji Tsuji; Rafaela Jesus-Santos; Osório Abath-Neto; et al. (Human Genetics, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

Effect of replacing soybean meal with peanut meal on milk production and fat composition in lactating dairy cows - Flávio Soares dos Santos; Ricardo Dias Signoretti; Juliana Silva de Oliveira; Gabriel Teodoro da Silva; Marcelo de Oliveira Alves Rufino; Carla Giselly de Souza; Jessyca Karen Pinheiro; Severino Gonzaga Neto (Tropical Animal Health and Production, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

A wide spectrum of neurological manifestations in pediatrics patients with the COVID-19 infection: a case series - Mariana Braatz Krueger; Raquel Carvalho Montenegro; Pablo Picasso de Araújo Coimbra; Luanna de Queiroz Lemos; Regiane Martins Fiorenza; Carla Jéssica da Silva Fernandes; Mariana Santos Leite Pessoa; Cleonísio Leite Rodrigues; Camilla Gomes da Cruz; Verlene de Araújo Verdiano; Fernanda Montenegro de Carvalho Araújo; Pedro Braga-Neto; et al. (Journal of NeuroVirology, 2021)

Acute and chronic lithium treatment increases Wnt/β-catenin transcripts in cortical and hippocampal tissue at therapeutic concentrations in mice - Vanessa J. De-Paula; Carla Cristine C. dos Santos; Maria Carolina A. Luque; Taccyana M. Ali; Jorge E. Kalil; Orestes V. Forlenza; Edecio Cunha-Neto (Metabolic Brain Disease, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Sugarcane Juice with Co-encapsulated Bifidobacterium animalis subsp. lactis BLC1 and Proanthocyanidin-Rich Cinnamon Extract - Augusto Tasch Holkem; Edmur José Santos Neto; Megumi Nakayama; Clitor J. F. Souza; Marcelo Thomazini; Fabio Augusto Gallo; Marluci Palazzolli da Silva; Laura de Queiroz Bomdespacho; Carla Giovana Luciano; Izabel Cristina Freitas Moraes; Rodrigo Rodrigues Petrus; Carmen S. Favaro-Trindade (Probiotics and Antimicrobial Proteins, 2020)

Guanosine and GMP increase the number of granular cerebellar neurons in culture: dependence on adenosine A2A and ionotropic glutamate receptors - Helena Decker; Tetsade C. B. Piermartiri; Cláudia B. Nedel; Luciana F. Romão; Sheila S. Francisco; Tharine Dal-Cim; Carina R. Boeck; Vivaldo Moura-Neto; Carla I. Tasca (Purinergic Signalling, 2019)

The citrus flavanone naringenin attenuates zymosan-induced mouse joint inflammation: induction of Nrf2 expression in recruited CD45+ hematopoietic cells - Allan J. C. Bussmann; Sergio M. Borghi; Tiago H. Zaninelli; Telma S. dos Santos; Carla F. S. Guazelli; Victor Fattori; Talita P. Domiciano; Felipe A. Pinho-Ribeiro; Kenji W. Ruiz-Miyazawa; Antonio M. B. Casella; Josiane A. Vignoli; Doumit Camilios-Neto; et al. (Inflammopharmacology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Divergent coronaviruses detected in wild birds in Brazil, including a central park in São Paulo - Carla M. Barbosa; Edison L. Durigon; Luciano M. Thomazelli; Tatiana Ometto; Roberta Marcatti; Marcello Shiavo Nardi; Daniel M. de Aguiar; João Batista Pinho; Maria Virginia Petry; Isaac Simão Neto; Patrícia Serafini; Roberta Costa Rodrigues; et al. (Brazilian Journal of Microbiology, 2019)

Negative inotropism of terpenes on guinea pig left atrium: structure-activity relationships - Carla M. L. Vasconcelos; Ingrid S. N. Oliveira; José N. A. Santos; Américo A. Souza; José E. R. Menezes-Filho; Júlio A. Silva Neto; Tamires C. Lima; Damião P. de Sousa (Natural Product Research, 2018)

Description of Hyphopichia buzzinii f.a., sp. nov. and Hyphopichia homilentoma comb. nov., the teleomorph of Candida homilentoma - Lucas R. Ribeiro; Ana R. O. Santos; Marizeth Groenewald; Maudy Th. H. Smith; Carla A. Lara; Aristóteles Góes-Neto; Noémie Jacques; Cécile Grondin; Serge Casaregola; Marc-André Lachance; Carlos A. Rosa (Antonie van Leeuwenhoek, 2017)

Robust Memories of Individual Identity in Ant Queens - André Rodrigues de Souza; Luiza Carla Barbosa Martins; Carlos Alberto Mourão-Júnior; José Eduardo Serrão; José Lino-Neto (Journal of Insect Behavior, 2014)

Erratum to: NMDA Preconditioning Attenuates Cortical and Hippocampal Seizures Induced by Intracerebroventricular Quinolinic Acid Infusion - Samuel Vandresen-Filho; Alexandre A. Hoeller; Bruno A. Herculano; Marcelo Duzzioni; Filipe S. Duarte; Tetsadê C. B. Piermartiri; Carina R. Boeck; Thereza C. M. de Lima; José Marino-Neto; Carla I. Tasca (Neurotoxicity Research, 2013)

NMDA Preconditioning Attenuates Cortical and Hippocampal Seizures Induced by Intracerebroventricular Quinolinic Acid Infusion - Samuel Vandresen-Filho; Alexandre A. Hoeller; Bruno A. Herculano; Marcelo Duzzioni; Filipe S. Duarte; Tetsadê C. B. Piermartiri; Carina C. Boeck; Thereza C. M. de Lima; José Marino-Neto; Carla I. Tasca (Neurotoxicity Research, 2013)

Hand dominance during constant force isometric contractions: evidence of different cortical drive commands - Rafael Pereira; Ivna Vidal Freire; Cláudia Virgínia Galindo Cavalcanti; Carla Patrícia Novais Luz; Osmar Pinto Neto (European Journal of Applied Physiology, 2012)

Antioxidant treatment protects against matrix metalloproteinase activation and cardiomyocyte injury during acute pulmonary thromboembolism - Ozelia Sousa-Santos; Evandro M. Neto-Neves; Karina C. Ferraz; Carla S. Ceron; Elen Rizzi; Raquel F. Gerlach; Jose E. Tanus-Santos (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Quercetin restores plasma nitrite and nitroso species levels in renovascular hypertension - Marcelo F. Montenegro; Evandro M. Neto-Neves; Carlos A. Dias-Junior; Carla S. Ceron; Michele M. Castro; Valeria A. Gomes; Alexandre Kanashiro; Jose E. Tanus-Santos (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Cytogenetic survey of species of two distinct genera of Iberian nases (Cyprinidae, Leuciscinae) that hybridize extensively in nature. I. Evidence of a similar and conserved chromosome pattern with some few species-specific markers at macro-structural level - Carla Pereira; Américo Neto; Maria João Collares-Pereira (Genetica, 2009)